2014
DOI: 10.1016/j.jvs.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of grade I-II blunt traumatic aortic injury

Abstract: Introduction Endovascular aortic repair has revolutionized the management of traumatic blunt aortic injury (BAI). However, debate continues about the extent of injury requiring endovascular repair, particularly with regard to minimal aortic injury (MAI). Therefore, we conducted a retrospective observational analysis of our experience with these patients. Methods We retrospectively reviewed all BAI presenting to an academic Level I trauma center over a ten-year period (2000–2010). Images were reviewed by a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 21 publications
1
58
1
5
Order By: Relevance
“…Furthermore, in contrast to previous studies, our survey showed considerable increased risk assessment scores for the pre-hospital phase for all subgroups. Du Bose et al and Demetriades et al demonstrated lower values for the ISS and for GCS as well as lower rates of hypotension on admission compared to this study [7, 8, 20]. In addition, a higher rate of conservative treatment for grade IV injuries was observed, which might be evaluated as palliative therapy for fatal injured persons, finally resulting in a higher mortality rate.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Furthermore, in contrast to previous studies, our survey showed considerable increased risk assessment scores for the pre-hospital phase for all subgroups. Du Bose et al and Demetriades et al demonstrated lower values for the ISS and for GCS as well as lower rates of hypotension on admission compared to this study [7, 8, 20]. In addition, a higher rate of conservative treatment for grade IV injuries was observed, which might be evaluated as palliative therapy for fatal injured persons, finally resulting in a higher mortality rate.…”
Section: Discussionsupporting
confidence: 42%
“…This observation is surprising, as the risk for rupture for BTAI grade I and II is generally estimated low and previous studies recommended medical treatment for patients suffering from grade I and II BTAI [7, 20]. Osgood et al described a low progression rate of medical treated grade I and II BTAI within a follow up period of 86 days [20]. However, the patients in the present study who received medical treatment, displayed an AIS > 3 and a GCS <8 more frequently as well as a higher rate of CPR compared to those receiving surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to treatment varies from one unit to another, in spite of several attempts to bring practices in line [17].…”
Section: Which Invasive Treatment Should Be Offered?mentioning
confidence: 99%
“…44 Although precise classification of an ATAI into one of these types based on CT may be difficult, radiologists should be aware of this classification scheme because it can inform prognosis, guide treatment, and determine the need for follow-up imaging. 45 What the Referring Clinician Needs to Know: Traumatic Aortic Injury Classification …”
Section: Acute Traumatic Aortic Injurymentioning
confidence: 99%